Grammatical structures of emoji in Japanese-language text conversations - Sekine, Kazuki; Ikuta, Manaka (Cognitive Research: Principles and Implications, 2024)
Emojis have become a ubiquitous part of everyday text communication worldwide. Cohn et al. (Cognit Res Princ Implic 4(1):1–18, 2019) studied the grammatical structure of emoji usage among English speakers and found a correlation between the sequence of emojis used and English word order, tending towards an subject–verb–object (SVO) sequence. However, it remains unclear whether emoji usage follows a universal grammar or whether it is influenced by native language grammar. Therefore, this study explored the potential influence of Japanese grammar on emoji usage by Japanese speakers. Twenty adults, all native Japanese speakers, participated in pairs. In Experiment 1, participants engaged in conversations through Google Hangouts on iPads. The experiment consisted of four conversation rounds of approximately 8 min each. The first two rounds involved one participant using only written Japanese and the other using only emojis and punctuation, with roles reversed in the second round. The third round required both participants to use only emojis and punctuation. The results indicated that participants preferred subject–object–verb (SOV) or object–verb (OV) sequences, with OV patterns being more common. This pattern reflects a distinctive attribute of Japanese grammatical structure, marked by the frequent omission of the subject. Experiment 2 substituted emojis for words, showing nouns were more commonly replaced than verbs due to the difficulty in conveying complex meanings. Reduced subject replacements again emphasised Japanese grammatical structure. In essence, emoji usage reflects native language structures, but complexities are challenging to convey, resulting in simplified sequences. This study offers insights for enhancing emoji-based communication and interface design, with implications for translation and broader communication.